Anterior Hip Replacement From Origin to Current Advanced Techniques - Matta, Joel M.; Sah, Alexander P.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
Anterior hip replacement is a surgical approach that has dramatically changed the landscape of modern hip replacement. The approach is common to orthopedic trauma surgery, but it has been rapidly adopted in recent years for hip replacement as well. Its proposed benefits as a muscle-sparing surgery include less tissue trauma, faster recovery, and fewer hip precautions. While the technique can be challenging during initial learning and early adoption, the approach continues to increase in utilization in the U.S. every year because of these benefits. Understanding the initial development of the anterior surgical approach for hip replacement creates the foundation to better understand its modern clinical benefits and possibilities with advanced techniques. Furthermore, a detailed description of the reasoning behind the continued developments of the anterior approach helps in understanding the key elements needed to obtain the most successful outcomes. With the continued adoption of this technically challenging technique, there is a need for a comprehensive resource for newly adopting surgeons and surgeons in training, but also for experienced surgeons looking to enhance their skill sets. Written by experts in the field, this book presents the tips and tricks learned after years of experience by a wide spectrum of surgeons. Parts 1 and 2 describe the origin and background of the anterior approach for hip replacement, with early lessons learned, important tips when training others, and how to master the operating table and c-arm. Parts 3 and 4 cover hip biomechanics and variations on techniques and technologies, respectively, while part 5 is a unique compilation of surgeons' perspectives on managing common aspects of the approach. Revision surgery is described in part 6, and future directions for the technique are discussed in part 7, along with emerging navigation and technologies. Every year, there is an increasing number of orthopedic surgeons learning and adopting the anterior hip approach who would benefit from the resources in this book, which will serve as a critical learning tool for training surgeons and also as the go-to reference for optimizing current use and advancing future possibilities of the approach.
Part 1. The Origins of the Anterior Hip Surgical Approach -- 1. The French Beginning and Judet School of the Anterior Approach -- 2. My French and American Beginning and Evolution of the Anterior Approach -- Part II. The Anterior Approach: An Established and Repeatable Technique -- 3. The Anterior Approach Surgical Technique for Total Hip Arthroplasty: The Matta Method of 2020 -- 4. Understanding the Modern Surgeon s Transition to Anterior Hip Replacement -- 5. The Learning Curve for the Anterior Approach: Early, Middle, and How It Continues -- 6. Introducing the Direct Anterior Approach (DAA) at a Swiss University Hospital -- 7. Challenges in Anterior Approach Education -- 8. Why I Favor a Standard Incision and Keys to Exposure for the Anterior Approach -- 9. Anterior Approach to the Hip Through the Oblique Bikini Incision -- 10. My Keys to Getting the Acetabulum Right with the Anterior Approach: Exposure, Preparation, Sizing, Position, Stability -- 11. My Keys to Getting the Femur Right with the Anterior Approach: Exposure, Preparation, Sizing, Depth of Insertion of Stem, Ball Head, Stability -- 12. Diagnosing and Managing Complications from the Anterior Approach -- 13. Tips and Tricks for Your First Anterior Hip Replacement -- 14. OR Efficiency: Radical Time Transparency and Operational Excellence -- 15. Results of the Direct Anterior Approach for Total Hip Arthroplasty -- 16. Difficult Cases in Primary Anterior Total Hip Arthroplasty -- 17. Direct Anterior Approach THA for Treatment of Femoral Neck and Acetabular Fractures -- 18. Anterior Approach Total Hip Arthroplasty Following Previous Femoral and Acetabular Fractures -- Part III. Hip Biomechanics: What Are We Trying to Achieve? -- 19. Normal Hip Biomechanics -- 20. Key Concepts and Methods for Acetabular Positioning -- 21. Understanding Leg Length and Offset -- Part IV. The Anterior Approach: The Variation of Techniques and Technologies -- 22. The Anterior Approach: From Robert Judet s Work to AMIS® (Anterior Minimally Invasive Surgery) -- 23. The History of the Direct Anterior Approach in Innsburck -- 24. The Direct Anterior Approach on a Standard Table in Zurich -- 25. A Hybrid Technique with a Standard Table and Mechanical Leg Holder -- 26. My Continued Evolution of the Anterior Approach -- Part V. Controversies in the Anterior Approach: Surgeon Perspectives -- 27. The Orthopedic Table versus the Standard OR Bed for the Anterior Approach -- 28. Handling the Hip Capsule with the Anterior Approach: Repair versus Capsulectomy -- 29. Judging Leg Length and Offset with the Anterior Approach: Clinical Evaluation versus Fluoroscopy -- 30. Does Pelvic Tilt Change Anything with the Anterior Approach? -- 31. Getting Correct Cup Position with the Anterior Approach: Bony Landmarks versus X-ray versus Computer Guidance -- 32. Stem Choice for Anterior Approach Total Hip Arthroplasty: Surgeon Perspectives -- 33. Hip Resurfacing Arthroplasty Using the Hueter-Anterior Approach -- Part VI. Revision Surgery Using the Anterior Hip Approach -- 34. Revision Surgery Exposure Techniques for the Anterior Hip Approach, Including Osteotomies -- 35. Complex Femoral Revision Using the Direct Anterior Hip Approach -- 36. Femoral Revision Total Hip Arthroplasty Using the Direct Anterior (Hueter) Approach -- 37. Complex Acetabular Reconstruction Using the Direct Anterior Approach -- 38. Treatment of Acute and Late Infections Using the Direct Anterior Approach -- Part VII. Future Directions in Techniques and Technology for the Anterior Approach -- 39. Navigation Technologies for the Anterior Approach in Total Hip Arthroplasty -- 40. Robotic Total Hip Replacement with Direct Anterior Approach -- 41. Problems to Solve and Potential Future Directions for Anterior Approach Total Hip Arthroplasty.
Keywords: Orthopedics; Orthopaedics; Arthroplasty, Replacement, Hip -- methods